Assessing Legal Consistency in Decentralized Policy Implementation Across Newly Established Regions - Sri Yulianingsih (Perkara : Jurnal Ilmu Hukum dan Politik, 2025)
The concept of decentralization has gained popularity as a means to enhance regional self-governance, but the most recent regions established must cope with the challenge of legal consistency in policy application. The objective of the current research is to evaluate the legal consistency of decentralized policy implementations in newly created regions by examining the relationship between the national government's legal norms and local policy practices in these areas. The research employs a qualitative socio-legal method, using a comparative case study approach involving some newly autonomous regions. The data for the research were gathered through analysis of legal documents, policy records, and in-depth interviews with key regional policy actors; the researchers also used thematic and comparative analyses to work through the data. The results of the research show that legal consistency remains irregular, with inconsistencies occurring mainly during implementation rather than in the drafting stage. Differences in institutional capacity and varying understandings of legal responsibilities are the main factors driving these inconsistencies. The study makes a significant contribution to the understanding of decentralization by placing the spotlight on legal consistency as a crucial bridge between the normative frameworks and policy practice. It recommends that the effective functioning of decentralization depends not only on coherent legal arrangements but also on strong institutional mechanisms to ensure consistent implementation at the regional level.